THE CONTROVERSY OF SOCIAL MEDIA AS A LEARNING MEDIUM BETWEEN OPPORTUNITIES FOR STRENGTHENING DIGITAL LITERACY AND THE RISK OF DISINFORMATION - Amali, Fauzi Iqbal; Zaini, Abdul Wahid; Khaer, Abu; Furqan, Moh; Yaqin, Moh Ainol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study investigates the controversies surrounding using social media as an educational tool, focusing on its potential to enhance digital literacy and the risks associated with misinformation. As social media platforms increasingly influence educational practices, this study explores how these platforms can be leveraged to strengthen digital literacy skills among students while addressing the challenges posed by misinformation. The study aims to answer three main questions: How is social media used as an educational tool to enhance digital literacy? What factors contribute to the spread of misinformation in academic contexts? Moreover, what strategies can be implemented to mitigate misinformation's negative impacts while maximizing social media's educational benefits? The findings suggest that while social media has significant potential to enhance digital literacy, spreading misinformation remains a critical concern. By addressing these issues, this study offers valuable insights for educators, policymakers, and social media users better to navigate the complex relationship between social media and education, thereby fostering a more informed and savvy generation of digital learners.